The cGAS-STING pathway for DNA sensing - Xiao, T Sam; Fitzgerald, Katherine A (Molecular cell, 2013)
The nucleotidyl transferase cGAS, its second-messenger product cGAMP, and the cGAMP sensor STING form the basic mechanism of DNA sensing in the cytoplasm of mammalian cells. Several new reports now uncover key structural features associated with DNA recognition by cGAS and the catalytic mechanisms of cGAMP generation. Concurrent studies also reveal unique phosphodiester linkages in endogenous cGAMP that distinguish it from microbial cGAMP and other cyclic dinucleotides. Together, these studies provide a new perspective on DNA recognition in the innate immune system.